Strategi Komunikasi Interpersonal dalam Meningkatkan Promosi pada Perguruan Tinggi X di Jakarta - Esi Hairani (Qiro'ah : Jurnal Pendidikan Agama Islam, 2018)
Competition between universities in recruiting students is increasingly high, the purpose of this study is to analyze communication strategies in order to improve promotion in x universities in Jakarta. The subject of the promotion team and are the ranks of leaders and utilize the role of alumni, stake holders and students. Then analyzed by data triangulation. The results of the study show that the program promoting campus X to be a brand image as the only Al-Qur'an college specifically for X college students in Jakarta has succeeded but the promotion program has not been maximized. Indicators are characterized by many prospective students who seek more information from various sources. So that affects the number of students who register. The cause of promotion ineffectiveness can be seen from the lack of handling and special attention to promotional programs. The cause can be seen from the element of the leadership role, coordination and the absence of a promotion team. The most common obstacles in promotion are lack of funds, so that promotion programs on this campus have so far not been systematic. Efforts to eliminate funding barriers on campus X such as several promotional steps to take advantage of opportunities indirectly where campus X is involved, among others, are MTQ and moments at religious events. The advantages that can make Campus X in Jakarta still survive are the only tertiary education institutions specifically for women. Where its competitors are still very rare, and the development of Islam that is quite good makes the current public interest in learning the Sciences of the Qur'an quite high.